Student Entrepreneurial Readiness with Self-Efficacy as an Intervening Variable - Andika Isma; Muhammad Rakib; Muh Yahya; Andi Naila Quin Azizah Alisyahbana; Ilham Abu (Universitas Negeri Makassar, 2023)
This study aims to test the entrepreneurial readiness model by presenting self-efficacy as an intervening variable that mediates the relationship between entrepreneurial attitudes and entrepreneurial knowledge. In addition, seven hypotheses were proposed in this study to determine the direct effect between the independent variables of entrepreneurial attitude and entrepreneurial knowledge, through the intervening self-efficacy variable on the dependent variable of entrepreneurial readiness. The population in this study were all students of the Entrepreneurship Study Program, Universitas Negeri Makassar, totaling 306 students and a total sample of 196 respondents, which was generated using a proportional random sampling technique. Data collection by questionnaire, data analysis through Path Analysis. Based on the results of research that has been done, directly and indirectly through self-efficacy, entrepreneurial attitudes and entrepreneurial knowledge have a positive and significant relationship to student interest in entrepreneurship. This is the basis that in this study, student entrepreneurship readiness is largely determined by the attitude and knowledge of entrepreneurship, both directly and through self-efficacy.